Strategy Strengthening Quality Management in Madrasah through Quality Cost - Syahru Romadhon, Muhammad; Padil, Moh.; Aminatuz Zuhriyah, Indah (Ar-Rosikhun: Jurnal Manajemen Pendidikan Islam, 2024)
This study aims to examine the application of the concept of quality costs in strengthening quality management in Madrasah. This concept involves four main aspects, namely prevention costs, appraisal costs, internal failure costs, and external failure costs. This study uses a qualitative research method with a literature study approach, by collecting data through literature reviews from various sources such as books, scientific articles, and relevant journals. The implementation of quality costs can help Madrasahs in improving operational efficiency, reducing waste of resources, and ensuring that the quality of education produced is in accordance with community expectations. This study found that by managing quality costs in a structured manner, Madrasahs can improve the quality of learning, improve the image of the institution, and become more competitive. In addition, this study also proposes the importance of improving communication and transparency with the community, as well as routine maintenance of facilities as a strategy to strengthen quality management. This study suggests that further research explores the long-term impacts of implementing quality costs and involves more stakeholders in evaluating the success of its implementation.